Familial narcolepsy in the Lipizzaner horse: a report of three fillies born to the same sire - Ludvikova, Eva; Nishino, Seiji; Sakai, Noriaki; Jahn, Petr (The Veterinary quarterly, 2012)
The occurrence of sleep disorder in three half sibling Lipizzaner is described. Sleepiness, swaying, stumbling, carpal joints buckling and falling down onto the carpal joints had been present since early foal age in all of them. Clinical signs had gradually reduced since the age of 2 years in cases 1 and 3. Sleepiness was induced by going out from the stable in adulthood. A physostigmine test was performed in all three affected horses and produced positive results in cases 1 and 3. The result of the test in case 2 was unclear due to the almost continuous sleepiness of the foal. Hypocretin-1 concentration in the cerebrospinal fluid was established using a standardised radioimmunoassay in case 1 (317.85 pg/mL), case 2 (303.43 pg/mL) and five adult control horses (275.2 ± 47.9 [SD] pg/mL) and was considered as normal in all horses. The sire of the affected horses has had 19 other registered offspring who did not show clinical signs of sleep disorder and also dams of all three cases produced healthy foals. Based on the demographic and clinical data together with the responses to the physostigmine challenges, the diagnosis of familial equine narcolepsy was made.
Keywords: narkolepsie; nemoci koní; Animals; neuropeptidy; Horses; Narcolepsy; Female; zvířata; intracelulární signální peptidy a proteiny; Neuropeptides; Intracellular Signaling Peptides and Proteins; Horse Diseases; ženské pohlaví; Physostigmine; fysostigmin; koně